Uncovering the affective turmoil during opportunity recognition and exploitation: a nonlinear approach - Santos, S. C.; Caetano, A.; Costa, S.; Rueff Lopes, R.; Junça Silva, A.; Neumeyer, X. (Journal of Business Venturing Insights, 2020)
This study explores the affective turmoil experienced by nascent entrepreneurs during opportunity recognition and exploitation. Based on the affect circumplex model, we employed nonlinear methods to identify configurations of affect that emerge during these early stages of the entrepreneurial journey. We analyzed data from 50 nascent entrepreneurs using Artificial Neural Networks (ANNs) trained with twenty affect dimensions as input variables and opportunity recognition and opportunity exploitation as outcomes. Results show that nascent entrepreneurs experience different affect configurations during opportunity recognition and exploitation. While four configurations of affect emerged associated with opportunity recognition and exploitation, their nature and importance to the experienced event are significantly different. Specifically, “active screening” is the most important configuration of affect during opportunity recognition, while “vigilant” is the most important during opportunity exploitation. We posit that nonlinear methods can help to uncover the affective turmoil experienced by entrepreneurs during a particular event. These findings provide new insights on how affect associates differently with cognition during the early stages of entrepreneurship.